The implementation of independent curriculum on mover schools - Setiawan Edi Wibowo; Bambang Saptono; Agung Hastomo; Herwin Herwin; Amalia Rizki Ardiansyah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
This research aims to describe the implementation of independent curriculum-based learning in mover schools. This research used a qualitative approach. The type of research used is phenomenology. The subjects of this study were selected based on purposive considerations. The participants of this study were targeted representatives of principals, teachers, students, and the relevant communities. Data collection in this study was carried out using interviews, observations, and documentation. The data was collected based on the needs of the research topic, namely independent curriculum-based learning in mover schools. The data of this study were analyzed using qualitative analysis techniques in the form of interactive analysis. The results of this study, one of the driving schools has implemented an independent curriculum. This can be seen from several key aspects of the independent curriculum, namely 1) the flow of learning objectives, 2) learning scenarios, 3) learning media that contain elements of TPACK, 4) Student Worksheets, and 5) the evaluation used. This can be used as a reference in the implementation of the independent curriculum, which in several schools is still trying to find the best pattern in its application in order to achieve the desired educational and learning goals.